The Effect of Quillbot on The Eleventh-Grade Students’ Writing Skills and Academic Integrity at Senior High School - Ayu Swati Pramitha Yuliandari, Ketut; Ratminingsih, Ni Made; Hery Santosa, Made (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the effect of QuillBot on the writing skills and academic integrity of eleventh-grade students. This quantitative study addresses three main questions: 1) Is there any simultaneous significant effect of the use of the QuillBot on eleventh-grade students’ writing skills and academic integrity? 2) Is there any significant effect of the use of the QuillBot on eleventh-grade students’ writing skills? and 3) Is there any significant effect on the use of the QuillBot for eleventh-grade students’ academic integrity? Data were collected through writing tests and academic integrity questionnaire, with analysis conducted using MANOVA. The findings indicate that QuillBot significantly improves students’ writing skills by enhancing clarity, coherence, and accuracy. Furthermore, QuillBot influences academic integrity by promoting ethical writing practices, such as proper paraphrasing and plagiarism detection. The study concludes that is a valuable tool for improving both writing skills and maintaining academic integrity in educational settings when it is used responsibly and under supervision. Recommendations are provided for educators on integrating QuillBot into their teaching strategies to maximize its benefits while minimizing potential misuse.